Rekonstruksi Sistem Presidential Threshold dalam Sistem Pemilu di Indonesia: (Studi Perbandingan Sistem Presidential Threshold Indonesia dan Brazil) - Sinta Devi Ambarwati; M. Roziq Saifulloh; Stella M.S. Aritonang (CV Rewang Rencang, 2020)
Elections that are hereinafter referred to as elections are one part of the process as well as the result of a democratic system based on the doctrine of